Examining Spring and Autumn Phenology in a Temperate Deciduous Urban Woodlot - (:unkn) unknown (My University, 2013)
This dissertation is an intensive phenological study in a temperate deciduous urban woodlot over six consecutive years (2007-2012). It explores three important topics related to spring and autumn phenology, as well as ground and remote sensing phenology. First, it examines key climatic factors influencing spring and autumn phenology by conducting phenological observations four days a week and recording daily microclimate measurements. Second, it investigates the differences in phenological responses between an urban woodlot and a rural forest by employing comparative basswood phenological data. Finally, it bridges ground visual phenology and remote sensing derived phenological changes by using the Normalized Difference Vegetation Index (NDVI) and Enhanced Vegetation Index (EVI) derived from the Moderate Resolution Imaging Spectro-radiometer (MODIS). The primary outcomes are as follows: 1) empirical spatial regression models for two dominant tree species - basswood and white ash - have been built and analyzed to detect spatial patterns and possible causes of phenological change; the results show that local urban settings significantly affect phenology; 2) empirical phenological progression models have been built for each species and the community as a whole to examine how phenology develops in spring and autumn; the results indicate that the critical factor influencing spring phenology is AGDD (accumulated growing degree-days) and for autumn phenology, ACDD (accumulated chilling degree-days) and day length; and 3) satellite derived phenological changes have been compared with ground visual community phenology in both spring and autumn seasons, and the results confirm that both NDVI and EVI depict vegetation dynamics well and therefore have corresponding phenological meanings.
Keywords: EVI; Intensive Observations; NDVI; Phenological Progression Model; Phenology; Temperate Deciduous Urban Woodlot